2021
DOI: 10.3389/fcell.2021.676142
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Ferroptosis Regulators With Regard to PD-L1 and Immune Infiltration in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is one of the tumor types with sensitivity to ferroptosis, and immunotherapy has emerged as a standard pillar for metastatic ccRCC treatment, while it remains largely obscure whether ferroptosis influences the tumor immune microenvironment in ccRCC. Based on available data in The Cancer Genome Atlas, divergent expression profiles of ferroptosis regulators were noted in ccRCC and normal tissues, and we also found that the ferroptosis regulators correlated with the PD-L1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Exhaustion of intracellular cystine or blocking of anti-programmed cell death protein 1/programmed death ligand 1 (anti-PD-1/PD-L1) immune checkpoint significantly enhanced T cell-mediated anti-tumor immunity and induced the ferroptosis of tumor cell. 85 At the same time, clinical data showed that among patients with melanin, the expression of cystine associated transporters SLC7A11 and SLC3A2 was negatively correlated with the number of CD8+T cells, IFN-γ expression level and patient prognosis. 86 Despite recently targeting lung cancer, the relationship between T cell and ferroptosis is uncertain.…”
Section: The Role Of Ferroptosis In Lung Cancermentioning
confidence: 99%
“…Exhaustion of intracellular cystine or blocking of anti-programmed cell death protein 1/programmed death ligand 1 (anti-PD-1/PD-L1) immune checkpoint significantly enhanced T cell-mediated anti-tumor immunity and induced the ferroptosis of tumor cell. 85 At the same time, clinical data showed that among patients with melanin, the expression of cystine associated transporters SLC7A11 and SLC3A2 was negatively correlated with the number of CD8+T cells, IFN-γ expression level and patient prognosis. 86 Despite recently targeting lung cancer, the relationship between T cell and ferroptosis is uncertain.…”
Section: The Role Of Ferroptosis In Lung Cancermentioning
confidence: 99%
“…RCC is a tumor with high sensitivity to ferroptosis, and a consensus clustering analysis on data from the TCGA, with regards to ferroptosis regulators, shows two independent clusters with different expressions of PD-L1 and immune infiltrate. The expression of PD-L1 was, therefore, used to understand a possible co-upregulation with a ferroptosis regulator and cysteinyl-tRNA synthetase (CARS), a described inhibitor of ferroptotic cell death shown to be highly expressed by RCC, correlating with the expression of PD-L1 and a worse prognosis and decreased overall survival, showing a possible connection between ferroptosis and the immune network orchestrated by the immune checkpoint molecules in RCC [ 74 ].…”
Section: Ferroptosis In Renal Cancersmentioning
confidence: 99%
“…In addition, the expressions of various ferroptosis-related genes can accurately predict the prognosis and survival outcome in ccRCC patients and are identified as potential prognostic biomarkers and therapeutic targets [ 11 , 13 ]. Moreover, triggering ferroptosis also enhances the efficiency of chemotherapy and immunotherapy for some refractory cases [ 14 , 15 ]. Based on these findings, it is promising and highly desirable to treat human ccRCC through inducing ferroptosis.…”
Section: Introductionmentioning
confidence: 99%